Power, Adaptation and Resistance in a Late-Modern Men's Prison - Crewe, Ben (The British journal of criminology, 2007)
Based on an ethnographic study of a medium-security UK men's training prison, this article has two main aims: to document the nature and experience of power in the late-modern prison, and to detail the ways in which prisoners adapt to these mechanisms of penal power. It is argued that although overt resistance is uncommon and prisoners generally appear highly compliant, this public transcript of consent comprises a range of prisoner orientations, from normative commitment to strategic, backstage resistance. In this respect, the article highlights the heterogeneous effects of penal power, and illustrates how the different components of prison social order are expressed through a range of adaptations to the ends and techniques of contemporary imprisonment